Aging impact on canine extracellular vesicles production, size, and miRNA content - Clara Luna Marina; Alexandra Mazer Greuel; Lucas de O. Las-Casas; Evilly Lopes-Gomes; Sabrina Simplício de Araújo Romero Ferrari; Marcio Lourenço Rodrigues; Flavia C. G. dos Reis; Anamélia Lorenzetti Bocca; Simoneide Souza Titze-de-Almeida; Fernando Francisco Borges Resende; Fabiano José Ferreira de Sant’Ana; Ricardo Titze-de-Almeida (Veterinary Research Communications, 2026)
Increasing life expectancy has been accompanied by a higher prevalence of age-associated conditions, underscoring the need to better understand biological mechanisms of aging and to identify accessible biomarkers. Extracellular vesicles (EVs) are lipid-bilayer vesicles that mediate intercellular communication by transporting proteins, lipids, and regulatory RNAs, including microRNAs (miRNAs). Here, we investigated whether the abundance, morphology, and molecular cargo of plasma-derived EVs differ between young and senior dogs. Blood samples were obtained from 24 clinically healthy dogs in Gama (Federal District, Brazil), and plasma EVs were isolated by sequential centrifugation, filtration through a 0.22 μm filter, and ultracentrifugation. EVs concentration and size distribution were assessed by nanoparticle tracking analysis (NTA), morphology by transmission electron microscopy (TEM), and cargo by quantification of total protein and sterols using commercial assays. In addition, we quantified miR-19b, miR-29c, miR-7, miR-155, and miR-21 by Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). Senior dogs exhibited a lower plasma EV yield and greater size heterogeneity, with a higher proportion of larger EVs. Total protein and sterol content per starting plasma volume were reduced in the senior group; however, sterol normalized per EV was increased, consistent with compositional remodeling of circulating vesicles with age. Finally, EV-associated miRNA levels were reduced in senior dogs, particularly miR-19b and miR-29c. Collectively, these findings indicate that canine aging is associated with marked changes in plasma EV abundance, morphology, and cargo, indicating that EVs could represent a promising tool for investigating age-related disorders in dogs.

Toxicity and repellency of the monoterpenoids carvone and eucalyptol on Sitophilus zeamais: contact and fumigation-based interactions - Daniele Muniz dos Reis; Solange Maria de França; Davila Esmelinda Oliveira Silva; Mariano Oscar Aníbal Ibañez Rojas; Giovana Lopes da Silva; Leonardo Baltazar Cantanhede; Herus Pablo Firmino Martins; Guilherme Santos de Sousa; Ana Patrícia Rodrigues Teixeira dos Reis; Gutierres Nelson Silva; Paulo Roberto Ramalho Silva; Lúcia da Silva Fontes; et al. (Journal of Plant Diseases and Protection, 2026)
Corn is a globally important crop; however, pest infestations during storage represent a major challenge. The maize weevil, Sitophilus zeamais (Coleoptera: Curculionidae), is a primary pest of stored maize, commonly controlled through phosphine fumigation. Nevertheless, extensive reliance on this insecticide has led to the emergence of resistant populations. Thus, the objective of this study was to evaluate the contact and fumigant toxicity of the monoterpenoids carvone and eucalyptol against S. zeamais , addressing the previously unexplored contact toxicity and repellency of these compounds following impregnation into maize grains, as well as their effects on population growth, insect fresh weight, and grain mass consumption. Experiments were conducted under laboratory conditions (28 ± 2 °C, 60 ± 10% relative humidity and a 12 h photoperiod) using a completely randomized design. Lethal concentrations (LC₅₀ and LC₉₅) were determined for contact and fumigation bioassays, and the LC₅₀ values obtained in the contact tests were used in repellency assays. Carvone exhibited higher toxicity than eucalyptol in both bioassays. In the contact toxicity test, LC₅₀ values were 3.48 µL/20 g for carvone and 14.35 µL/20 g for eucalyptol, while in fumigation assays the LC₅₀ values were 7.68 µL/L and 59.56 µL/L, respectively. Both compounds showed strong repellent activity against S. zeamais , with LC₅₀ treatments attracting only 0.2 and 0.8 insects to eucalyptol- and carvone-treated grains, respectively, corresponding to repellency levels above 90%. The treatments significantly reduced adult emergence and resulted in negative instantaneous population growth rates (r i ranging from − 0.0255 to − 0.0512), indicating population decline. Grain weight loss was reduced to 1.6% for carvone and 0.9% for eucalyptol when LC₅₀ concentrations were applied. These results demonstrate that carvone and eucalyptol exhibit insecticidal and repellent properties and may represent promising alternative agents for the management of S. zeamais in stored maize.

Both Bacillus siamensis BACIII inoculation and its carrier medium influence root-associated fungal communities - Jefferson Brendon Almeida dos Reis; Sofia Coradini Schirmer; Alexandra Martins; Chiara Tawane Lauriola; Bianca Rodrigues Teixeira; Geovana Lívio de Macedo; Ana Julia Pereira Rodrigues; Amanda Ribeiro Fernandes de Brito; Vinicius Rodrigues Teodoro; Helson Mario Martins do Vale (Rhizosphere, 2026)

A living lab approach to urban water reuse: Coupling plant growth monitoring and social acceptance in university buildings - Ana Maria Barreiros; Iola Pinto; Alexandra Rodrigues; Maria Idália Gomes (Journal of Cleaner Production, 2026)

Chlorophyll a Fluorescence and Chloroplastidic Pigments as Indicators of Aluminum Toxicity in Hydroponic Lettuce - Antonio Rodrigues da Cunha Neto; Giselle Marcia de Melo; Alexandra dos Santos Ambrósio; Tainara Bettiol Westin; Christiane Augusta Diniz Melo; Silvino Guimaraes Moreira; Thiago Corrêa de Souza; Breno Régis Santos; Sandro Barbosa (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is a major limiting factor for plants, but its effects in hydroponic systems, particularly on chlorophyll and the photosystem, remain poorly understood. Among horticultural crops, lettuce is notable for its production versatility in diverse systems, which may be susceptible to exposure to this metal. Therefore, this study aimed to evaluate the effect of Al on the growth, tissue accumulation, chloroplastidic pigments, and photosystem of lettuce grown in a hydroponic system. For this purpose, lettuce plants (cv. Regina) were exposed to 0, 50, 100, 250, and 500 µM of aluminum nitrate in Hoagland solution. Tissue aluminum content, growth parameters, chloroplastidic pigments, and chlorophyll a fluorescence were evaluated from the 42nd to the 70th day after seedling emergence (DAE). Al accumulated preferentially in the roots. Translocation to the leaves was highest at 100 µM and decreased at higher concentrations. Growth was initially inhibited (day 42) at the highest concentrations, followed by a significant increase in biomass and leaf number (from day 56 onward) compared to the control. However, Al stress caused a progressive and dose-dependent reduction in chlorophyll a , b , and carotenoid contents. Fluorescence analysis on the 70th day revealed a drastic drop in photochemical efficiency under light (Fv’/Fm’) and the vitality index (Rfd), with an increase in non-photochemical quenching (qN). Although the lettuce showed increased biomass, possibly due to the fertilizing effect of nitrate (NO 3 ), this growth occurred at the expense of photosynthetic health, compromising photochemical efficiency and pigment content.

Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

Taxonomic and functional inferences of cultivable endophytic fungi in two endemic Cerrado plants: dominance of Diaporthe across contrasting host phenologies - Mayara Oliveira Sousa Rodrigues; Jefferson Brendon Almeida dos Reis; Alexandra Martins; Danilo Batista Pinho; Lorena Carneiro Albernaz; Helson Mario Martins do Vale (Folia Microbiologica, 2026)
Host phenology is an important determinant of the microbial community, yet how it shapes the evolution and function of endophytic fungi in native plants of the Cerrado remains poorly understood. We investigated cultivable foliar fungal communities in Connarus suberosus (evergreen) and Diospyros lasiocalyx (deciduous) using an integrative approach. A total of 365 isolates were obtained, and most belonged to the genus Diaporthe . Both host plants harbored communities with similar alpha and beta diversity patterns, characterized by high taxonomic dominance and consistent composition. Beta diversity analyses revealed no significant differences in community composition between host species (PERMANOVA, p > 0.05). The high abundance of Diaporthe in both hosts likely contributed to the observed compositional similarity. Phylogenetic community structure was consistent between hosts, characterized by stochastic assembly for most taxa. The only distinct signal was a significant phylogenetic clustering for the genus Diaporthe in the deciduous D. lasiocalyx (NTI = 0.75; p = 0.042), whereas Diaporthe in C. suberosus followed a stochastic pattern (NTI = -0.60; p = 0.677). For non-dominant genera, assembly rules remained stochastic in both host species ( p > 0.05). The bipartite network analysis indicated compartmentalization, with 72.4% of genera classified as specialists. Diaporthe showed significant negative correlations with Penicillium and Colletotrichum ( p < 0.001), indicating non-random association patterns among dominant taxa. Functionally, Mantel analyses indicated that variation in plant-pathogen and litter-saprotroph guilds was associated with taxonomic community structure. Overall, our results indicate that contrasting host phenologies had limited effects on the diversity and composition of cultivable foliar endophytic fungal communities. Instead, both hosts were characterized by similar community structures dominated by Diaporthe , with only a subtle phylogenetic signal detected for this genus in the deciduous host.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Evolution and emergence of the integrase inhibitor 231 insertion resistance mutation in an HIV-2 strain isolated in central Portugal - João Pereira-Vaz; Anália Carmo; Alexandra Mendes; Célia Morais; Ana Alves; Fernando Rodrigues; Vítor Duque (Virus Genes, 2026)

Traditional Chinese medicine techniques for the management of fibromyalgia: a systematic review of randomized controlled trials - Helena L. Silva; Andreia V. Santos; Alexandra B. Monteiro; Maria R. Sousa; Jorge Magalhães Rodrigues (Advances in Traditional Medicine, 2026)

WITHDRAWN: Inflammatory markers levels and clinical characteristics in COVID-19 susceptibility and severity: A cross-sectional multicentric study - Lucas C. Pedro; Camila O. Arent; Flávia S. Niero; Caion A. Rodrigues; Margarete D. Bagatini; Gabriela G. de Oliveira; Zuleide Maria Ignácio; Larissa Joaquim; Fabricia Petronilho; João Quevedo; Alexandra I. Zugno; Luciane B. Ceretta; et al. (Next Research, 2026)

Spatial heterogeneity in rainfall extreme trends across Santa Catarina, Brazil - Jéssica Aurora Bernardo; Jakcemara Caprario; Julia dos Santos da Silva; Patrícia Kazue Uda; Alexandra Rodrigues Finotti (Theoretical and Applied Climatology, 2026)
Understanding spatial patterns of extreme precipitation trends is essential for climate risk assessment, particularly in regions characterized by strong climatic heterogeneity and limited monitoring networks, where locally significant trends may be overinterpreted if field significance is not explicitly assessed. This study presents a regional analysis of trends in ten extreme precipitation indices calculated for each of 62 rainfall stations across Santa Catarina, southern Brazil, resulting in a total of 620 daily time series analyzed over a 45-year period (1976–2021). Local trends were assessed using the Mann–Kendall test and Sen’s slope estimator, while field significance was evaluated through the False Discovery Rate (FDR) procedure to control for the multiple-testing problem and reduce false detections. Results indicate that most series exhibit no statistically significant trends; however, among the 24 field-significant signals retained after FDR correction, increasing trends were twice as frequent as decreasing ones. Statistically robust changes were more consistently detected in intensity-related indices, such as R99p and SDII, whereas frequency indices (R25 and R50) and total annual precipitation (PRCPTOT) largely lost significance after multiplicity control. The spatial distribution of these field-significant trends is heterogeneous, with increasing signals concentrated in the Western Mesoregion and predominantly decreasing trends observed in the Northern Mesoregion, while other regions exhibit mixed patterns. These findings demonstrate the importance of explicitly addressing multiple testing in regional trend analyses and highlight the value of long-term, spatially representative daily rainfall observations for distinguishing robust regional signals from statistical noise. The results provide a consistent empirical basis for climate risk assessment and adaptation planning in southern Brazil, while emphasizing the need for region-specific approaches in studies of precipitation extremes.

Ecotoxicological Effect of Kappaphycus alvarezii Extract on Zea mays and Ceriodaphnia silvestrii - Lucas Adriano Moreira; Erika dos Santos Silva; Antonio Rodrigues da Cunha Neto; Anelise Vieira Rosa Fernandes da Silva; Alexandra dos Santos Ambrósio; João Vitor Barbosa Calvelli; Gabriela Ezequiel Costa Martins; Maria José dos Santos-Wisniewski; Breno Régis Santos; Sandro Barbosa (Bulletin of Environmental Contamination and Toxicology, 2026)
Marine algae are recognized as promising sources of natural biostimulants in agriculture, with potential applications in seed physiological conditioning. However, the environmental implications of their production, management, and disposal remain insufficiently addressed. This study evaluated the ecotoxicological effects of a commercial Kappaphycus alvarezii extract on Zea mays and Ceriodaphnia silvestrii . Conditioning assays with maize seeds were performed at extract concentrations of 0, 25, 50, 75, and 100%, assessing germination, vigor, and early seedling growth. Acute toxicity tests with C. silvestrii exposed individuals to 0.1–4% concentrations, and immobility was recorded to determine the median effective concentration (EC 50 ). Concentrations up to 50% did not impair germination, with 25% promoting significant vegetative growth, while higher concentrations reduced germination due to phytotoxicity. In C. silvestrii , 2.06% caused 50% mortality. These results demonstrate the dual role of algal extracts, highlighting agronomic potential alongside ecotoxicological risks, and reinforce the need for safe production, management, and environmentally responsible disposal practices to ensure sustainability.

Insights into chemical profile and leaf anatomy in the dioecious species Baccharis platypoda: sex-related differences and environmental patterns - Fábio Cassola; Guilherme Perez Pinheiro; Carina de Araujo; João Pedro Silvério Pena Bento; Guilherme Almeida Garcia Rodrigues; Alexandra Christine Helena Franklan Sawaya; Alex Aparecido Rosini Silva; Ingrid Koch; Adilson Sartoratto; Patrícia de Oliveira Carvalho; Juliana Lischka Sampaio Mayer (Protoplasma, 2026)

Seasonal biochemical fingerprints of outdoor cultivated Spirulina (Limnospira platensis) and Microchloropsis gaditana: insights into compositional and functional shifts - Diana Lopes; Ana S.P. Moreira; Tiago Conde; Andreia Ferreira; Kayane Oliveira; Alexandra Conde; Helena R. Rocha; Marta Coelho; Ana Gomes; Manuela Pintado; Ana Alexandra Ramos; Hugo Pereira; et al. (Algal Research, 2026)

Coarse particulate matter air pollution in Porto Metropolitan area, Portugal: time series analysis, trends and implications for public policies - Simone Georges El Khouri Miraglia; Ronan Adler Tavella; Daniela Debone; Rui Moreira Barbosa; Flavio Manoel Rodrigues da Silva Júnior; Clara Lopes Ribeiro; Simone Morais; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2026)
Air pollution remains a persistent environmental and public health concern in urban regions. This study presents a 22-year analysis (2001–2022) of coarse particulate matter (PM 10 ) concentrations across 15 monitoring stations in the Porto Metropolitan Area (PMA), Portugal. The stations, pre-classified by national authorities as traffic, background-urban, background-suburban, or industrial, were used to assess long-term temporal trends and spatial variability. Annual mean PM 10 concentrations were calculated and linear regression was applied to evaluate trends. Differences between station types were tested using statistical analysis. The results revealed consistent decline in PM 10 levels from the early 2000s to the mid-2010s, followed by stagnation or increases at several stations in the final years of the series. While higher concentrations were historically observed at traffic and industrial sites, no statistically significant differences in annual mean PM 10 concentrations were found between stations of different classifications or within classifications, even when comparing distinct time periods. This homogeneity suggests widespread regional exposure, likely driven by shared emission sources, atmospheric transport, and urban development patterns across the PMA. When compared to World Health Organization (WHO) air quality guidelines, exceedances were frequent and persistent. From 2001 to 2011, nearly all stations with valid data exceeded the 2005 guideline of 20 µg/m 3 . Between 2012 and 2020, the exceedances gradually decreased, although several stations still surpassed the guideline. However, under the 2021 WHO guideline (15 µg/m 3 ), all stations with valid data for 2021 and 2022 again exceeded the guideline. These findings highlight the need for integrated, long-term air quality policies. Clinical trial number: Not applicable.

Land use regulations assessment on the impacts on urban river systems in Florianópolis, southern Brazil - Paula Lidia Santana; Jakcemara Caprario; Patrícia Kazue Uda; Alexandra Rodrigues Finotti (Land Use Policy, 2026)

Cork stripping alters the seasonal carbon allocation patterns of Quercus suber in a dry year - Clara A. Pinto; Filipe Costa-e-Silva; Alexandra C. Correia; José Graça; Olfa Zarrouk; Teresa S. David; José C. Rodrigues; João S. Pereira; Maria Manuela Chaves; Carla Pinheiro (Forest Ecology and Management, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Method and composition for encapsulation and matrix of synthetic seeds of Kalanchoe daigremontiana (Raym.-Hamet & Perrier) A. Berger - Ana Paula de Souza Bento; Marília de Souza Lopes Alves; Arlinda de Jesus Rodrigues Resende; Giovana Esteves; Alexandra dos Santos Ambrósio; Antonio Rodrigues da Cunha Neto; Breno Régis Santos (Vegetos, 2025)

A mechanistically-anchored and human stem cell-based in vitro test battery for assessing liver steatogenic potential of chemicals - Anouk Verhoeven; Alexandra Gatzios; Robim M. Rodrigues; Julen Sanz-Serrano; Joery De Kock; Mathieu Vinken; Tamara Vanhaecke (Toxicology, 2025)

Integrative molecular and taxonomic techniques reveal larval fish biodiversity patterns in the Azores UNESCO biosphere reserves - Milene Alexandra Guerreiro; Ana Veríssimo; Filipe Costa; Manuel J. Rodrigues; Miguel Ângelo Pardal; Ana Lígia Primo; Filipe Martinho (Estuarine, Coastal and Shelf Science, 2025)

Replacement of fish oil with Tenebrio molitor larvae oil in diets for juvenile silver catfish (Rhamdia quelen) - Kimberly Costa Dias; Alexandra Pretto; Fabio de Araújo Pedron; Giovani Taffarel Bergamin; Thiago Signori Gralha; Cristiano Miguel Stefanello; Ana Carolina Hadlich Xavier; Roger Wagner; Rafael Yutaka Kuradomi; Fernanda Rodrigues Goulart Ferrigolo; Francielli Weber Santos Cibin; Carlos Frederico Ceccon Lanes (Aquaculture International, 2025)

Whey protein and probiotic supplementation ameliorates DSS-induced colitis in mice - Amanda Ascanio; Jaqueline Cristina Galiardo; Eliane Vale da Silva; José Antônio Sampaio Zuanon; Luis Carlos Spolidorio; Letícia de Aquino Penteado; Priscila Marques Firmiano Dalle Piagge; José Fernando Rinaldi de Alvarenga; Alexandra Ivo de Medeiros; Daniel Rodrigues Cardoso; Daniela Cardoso Umbelino Cavallini (International Dairy Journal, 2025)

β-Glucan Alone or Combined with Lactobacillus acidophilus Positively Influences the Bacterial Diversity and Metabolites in the Colonic Microbiota of Type II Diabetic Patients - Jéssika Rodrigues Clementino; Louise Iara Gomes de Oliveira; Mateus Kawata Salgaço; Fellipe Lopes de Oliveira; Victoria Mesa; Josean Fechine Tavares; Ludmilla Silva-Pereira; Breno Vilas Boas Raimundo; Karen Cristina Oliveira; Alexandra Ivo Medeiros; Francyeli Araújo Silva; Katia Sivieri; et al. (Probiotics and Antimicrobial Proteins, 2025)

Unlocking biochemical profile of Chaetoceros calcitrans, Cylindrotheca fusiformis, and Nannofrustulum shiloi (Bacillariophyta) for nutritional and added-value applications - Ana S.P. Moreira; Helena R. Rocha; Susana Aveiro; Andreia S. Ferreira; Kayane Oliveira; Alexandra Conde; Marta Coelho; Alexandre M.C. Rodrigues; Natacha Coelho; Hugo Pereira; Ana Gomes; Manuela Pintado; et al. (Algal Research, 2025)

A population under smoke: fire events trigger severe air pollution in Portugal - Simone Georges El Khouri Miraglia; Daniela Debone; Clara Lopes Ribeiro; Rui Moreira Barbosa; Ronan Adler Tavella; Flavio Manoel Rodrigues da Silva-Júnior; Manuela Vieira da Silva; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2025)

Cumulative potential of Lactuca sativa L. and physiological and anatomical damage when exposed to lead - Antonio Rodrigues da Cunha Neto; Tainara Bettiol Westin; Alexandra dos Santos Ambrósio; João Vitor Barbosa Calvelli; Breno Régis Santos; Thiago Corrêa de Souza; Marília Carvalho; Sandro Barbosa (Environmental Science and Pollution Research, 2025)

Particle‐Associated Bacterioplankton Communities Across the Red Sea - Larissa Frühe; Shannon G. Klein; Carlos Angulo‐Preckler; Anastasiia Martynova; Taiba Alamoudi; Jacqueline V. Alva García; Silvia Arossa; Jessica Breavington; Sofia Frappi; Elisa Laiolo; Kah Kheng Lim; Anieka J. Parry; et al. (Environmental Microbiology, 2025)
Pelagic particle‐associated bacterioplankton play crucial roles in marine ecosystems, influencing biogeochemical cycling and ecosystem functioning. However, their diversity, composition, and dynamics remain poorly understood, particularly in unique environments such as the Red Sea. In this study, we employed eDNA metabarcoding to comprehensively characterise bacterioplankton communities associated with pelagic particles in a three‐dimensional assessment spanning depths from the surface to a depth of 2300 m along the full length of the eastern Red Sea within the exclusive economic zone of the Kingdom of Saudi Arabia. Our results reveal a diverse assemblage of taxa, with Pseudomonadota, Cyanobacteriota, and Planctomycetota being the dominant phyla. We identified pronounced spatial variability in community composition among five major Red Sea geographical regions, with a third of all amplicon sequence variants being unique to the Southern Red Sea in contrast to a relatively homogenous distribution along the water column depth gradient. Our findings contribute to a deeper understanding of microbial ecology in the Red Sea and provide valuable insights into the factors governing pelagic particle‐associated bacterioplankton communities in this basin.

Effect of bioactive compounds from culinary herbs against cholesterol thermo-oxidation in omelets during home cooking processes - Vanessa Sales de Oliveira; Davy William Hidalgo Chávez; Ormindo Domingues Gamallo; Rosane Nora Castro; Alexandra Christine Helena Frankland Sawaya; Geni Rodrigues Sampaio; Elisabeth Aparecida Ferraz da Silva Torres; Tatiana Saldanha (International Journal of Gastronomy and Food Science, 2024)

Hepatitis E virus prevalence among HIV-2 infected individuals in central Portugal - João Pereira-Vaz; Anália Carmo; Vítor Duque; Cristina Luxo; Ana Alves; Alexandra Mendes; Célia Morais; Cláudio Gaspar; Raquel Costa; Lurdes Correia; Fernando Rodrigues; Ana Matos (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

The role of culture in the representation of probiotic foods - Michele Christine Machado-Oliveira; Heber Rodrigues; Antonio Bisconsin-Junior; Gustavo H.T.A. Camillo; Héctor Sierra; Oluwadara Alegbeleye; Carlos Gomez-Corona; Dusanka Micetic-Turk; Luz Maria Paucar-Menacho; Alexandra A.I.A. Chincha; Andrea Gomez-Zavaglia; Mara Virginia Galmarini; et al. (Food Research International, 2024)

A quantitative weight-of-evidence method for confidence assessment of adverse outcome pathway networks: A case study on chemical-induced liver steatosis - Anouk Verhoeven; Jonas van Ertvelde; Joost Boeckmans; Alexandra Gatzios; Ramiro Jover; Birgitte Lindeman; Graciela Lopez-Soop; Robim M. Rodrigues; Anna Rapisarda; Julen Sanz-Serrano; Marth Stinckens; Sara Sepehri; et al. (Toxicology, 2024)

Shifts in plant functional groups along an aridity gradient in a tropical dry forest - Ana Cláudia Pereira de Oliveira; Alice Nunes; Maria Alexandra Oliveira; Rafael S. Oliveira; Renato Garcia Rodrigues; Cristina Branquinho (Science of The Total Environment, 2024)

The Coexistence of People and Bearded Capuchins (Sapajus libidinosus) in a Nonindustrial Ecosystem: An Assessment of Tourist and Local Perceptions in the Coastal Area of Maranhão, Brazil - Alexandra N. Hofner; Paulo Carvalho; Mariana Pissarra Matos; Andrea Presotto; Ricardo Rodrigues dos Santos; Roberta Salmi (International Journal of Primatology, 2024)

Consistent Symbiodiniaceae community assemblage in a mesophotic-specialist coral along the Saudi Arabian Red Sea - Silvia Vimercati; Tullia I. Terraneo; Carolina Bocanegra Castano; Federica Barreca; Benjamin C. C. Hume; Fabio Marchese; Mustapha Ouhssain; Alexandra Steckbauer; Giovanni Chimienti; Ameer A. Eweida; Christian R. Voolstra; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Introduction The Red Sea is a narrow rift basin characterized by latitudinal environmental gradients which shape the diversity and distribution of reef-dwelling organisms. Studies on Symbiodiniaceae associated with select hard coral taxa present species- specific assemblages and concordant variation patterns from the North to southeast Red Sea coast at depths shallower than 30 m. At mesophotic depths, however, algal diversity studies are rare. Here, we characterize for the first-time host-associated algal communities of a mesophotic specialist coral species, Leptoseris cf. striatus , along the Saudi Arabian Red Sea coast. Methods We sampled 56 coral colonies spanning the eastern Red Sea coastline from the Northern Red Sea to the Farasan Banks in the South, and across two sampling periods, Fall 2020 and Spring 2022. We used Next Generation Sequencing of the ITS2 marker region in conjunction with SymPortal to denote algal assemblages. Results and discussion Our results show a relatively stable coral species-specific interaction with algae from the genus Cladocopium along the examined latitudinal gradient, with the appearance, in a smaller proportion, of presumed thermally tolerant algal taxa in the genera Symbiodinium and Durusdinium during the warmer season (Fall 2020). Contrary to shallow water corals, our results do not show a change in Symbiodiniaceae community composition from North to South in this mesophotic specialist species. However, our study highlights for the first time that symbiont communities are subject to change over time at mesophotic depth, which could represent an important phenomenon to address in future studies.

Anti-inflammatory and antiproliferative activity of Helichrysum odoratissimum Sweet. against lung cancer - Tenille Esmear; Danielle Twilley; Velaphi Clement Thipe; Kattesh V. Katti; Vusani Mandiwana; Michel Lonji Kalombo; Suprakas Sinha Ray; Rirhandzu Rikhotso-Mbungela; Venugopal Reddy Bovilla; SubbaRao Madhunapantula; Lenka Langhanshova; Catarina Roma-Rodrigues; et al. (South African Journal of Botany, 2024)

A green method for anthocyanin extraction from Clitoria ternatea flowers cultivated in southern Brazil: Characterization, in vivo toxicity, and biological activity - Glória Caroline Paz Gonçalves; Alexandra Lizandra Gomes Rosas; Rafael Carneiro de Sousa; Thaís Regina Rodrigues Vieira; Thamyres César de Albuquerque Sousa; Tassiana Ramires; Tayse Ferreira Ferreira da Silveira; Lillian Barros; Wladimir Padilha da Silva; Álvaro Renato Guerra Dias; Elessandra da Rosa Zavareze; Adriana Dillenburg Meinhart (Food Chemistry, 2024)

Altered expression of Sialyl Lewis X in experimental models of Parkinson’s disease - Maria João Nunes; Andreia Neves Carvalho; Alexandra I. Rosa; Paula A. Videira; Maria João Gama; Elsa Rodrigues; Margarida Castro-Caldas (Journal of Molecular Medicine, 2024)
The mechanisms underlying neurodegeneration in Parkinson’s disease (PD) are still not fully understood. Glycosylation is an important post-translational modification that affects protein function, cell-cell contacts and inflammation and can be modified in pathologic conditions. Although the involvement of aberrant glycosylation has been proposed for PD, the knowledge of the diversity of glycans and their role in PD is still minimal. Sialyl Lewis X (sLeX) is a sialylated and fucosylated tetrasaccharide with essential roles in cell-to-cell recognition processes. Pathological conditions and pro-inflammatory mediators can up-regulate sLeX expression on cell surfaces, which has important consequences in intracellular signalling and immune function. Here, we investigated the expression of this glycan using in vivo and in vitro models of PD. We show the activation of deleterious glycation-related pathways in mouse striatum upon treatment with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), a toxin-based model of PD. Importantly, our results show that MPTP triggers the presentation of more proteins decorated with sLeX in mouse cortex and striatum in a time-dependent manner, as well as increased mRNA expression of its rate-limiting enzyme fucosyltransferase 7. sLeX is expressed in neurons, including dopaminergic neurons, and microglia. Although the underlying mechanism that drives increased sLeX epitopes, the nature of the protein scaffolds and their functional importance in PD remain unknown, our data suggest for the first time that sLeX in the brain may have a role in neuronal signalling and immunomodulation in pathological conditions. Key messages MPTP triggers the presentation of proteins decorated with sLeX in mouse brain. MPTP triggers the expression of sLeX rate-limiting enzyme FUT 7 in striatum. sLeX is expressed in neurons, including dopaminergic neurons, and microglia. sLeX in the brain may have a role in neuronal signalling and immunomodulation.

Microplastics ingestion and endocrine disrupting chemicals (EDCs) by breeding seabirds in the east tropical Atlantic: Associations with trophic and foraging proxies (δ15N and δ13C) - Diana M. Matos; J.A. Ramos; A.L.C. Brandão; Alexandra Baeta; Isabel Rodrigues; I. dos Santos; João Coentro; J.O. Fernandes; L.A.E. Batista de Carvalho; M.P.M. Marques; S.C. Cunha; S.H. Santos; et al. (Science of The Total Environment, 2024)

Impact of heat stress on genetic evaluation of oocyte and embryo production in Gir dairy cattle - Giovani Luis Feltes; Renata Negri; Fernanda Santos Silva Raidan; Alexandra Fabielle Pereira Viana; Luiz Fernando Rodrigues Feres; Virgínia Mara Pereira Ribeiro; Jaime Araújo Cobuci (Tropical Animal Health and Production, 2024)

First record of a live adult heteropod Firoloida desmarestia in the Red Sea - Carlos Angulo-Preckler; Alexandra Steckbauer; Isabel Armelles; Susana Agustí; Mattie Rodrigue; Vincent Pieribone; Mohammad Qurban; Carlos M. Duarte (Frontiers in Marine Science, 2023)
Observations are essential to explore and discover the ocean. The rapid advancements in technology have revolutionized our capacity to document the ocean and its diverse array of species, pushing the boundaries of our understanding further than ever before. The central Red Sea was exposed as part of the Red Sea Decade Expedition , which took place from 04 February to 18 June 2022 aboard the R/V OceanXplorer, using underwater submersibles. Here, for the first time in the Red Sea, we reported three observations of living Firoloida desmarestia specimens, one female and two male specimens, a heteropod from the Pterotracheidae family. This shell-less mollusk has been observed in the epipelagic zone of the world’s oceans, with the exception of polar regions, suggesting a global distribution for these observations. The two males were observed swimming in the water column, while the female was close to the seabed. All three observations were detected during the morning, raising the question if these organisms use vertical migrations to reach deep-sea waters during the daytime. However, no ROV or submersible dives were conducted at night. Our results show a depth range expansion for observations of this species in the Red Sea. Furthermore, as far as we know, no adults of F. desmarestia have been reported until now in the Red Sea. During the expedition, all three specimens were found at similar depths (350, 400, and 464.5 m depth), with the female being the deepest, thus confirming the eurybathic distribution of this species. The emerging technology is progressively enhancing our understanding of these enigmatic creatures and expanding our knowledge of their fascinating adaptations and ecological roles. In addition to our fieldwork, a literature search was performed to uncover any pre-existing observational records of this species to understand its global distribution and ecological significance.

Climate forcing on estuarine zooplanktonic production - Ana Lígia Primo; Carlos Cruz; Filipe Martinho; Milene Alexandra Guerreiro; Manuel J. Rodrigues; Miguel Pardal (Marine Pollution Bulletin, 2023)

Pharmacogenetics in early drug development for non-alcoholic steatohepatitis: missed chances and future opportunities - Joost Boeckmans; Alexandra Gatzios; Jörn M. Schattenberg; Robim M. Rodrigues; Vera Rogiers; Tamara Vanhaecke (Archives of Toxicology, 2023)

Forage based diet as an alternative to a high concentrate diet for finishing young bulls - Effects on growth performance, greenhouse gas emissions and meat quality - José Santos-Silva; Susana P. Alves; Alexandra Francisco; Ana Paula Portugal; Maria Teresa Dentinho; João Almeida; José Leandro Regedor da Silva; Letícia Fialho; Liliana Cachucho; Eliana Jerónimo; Ana Barradas; António Rodrigues; et al. (Meat Science, 2023)

Later prehistoric tin mining in the Ervedosa mine (Vinhais, Portugal): evidence and context - Emmanuelle Meunier; Filipa Dias; João Fonte; Alexandre Lima; Alexandra Rodrigues; Carlo Bottaini; Rui J. C. Silva; João P. Veiga; Manuel F. C. Pereira; Elin Figueiredo (Archaeological and Anthropological Sciences, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

The impacts of pink pepper (Schinus terebinthifolius Raddi) on fatty acids and cholesterol oxides formation in canned sardines during thermal processing - Carla Fernanda Targueta Barreira; Vanessa Sales de Oliveira; Davy William Hidalgo Chávez; Ormindo Domingues Gamallo; Rosane Nora Castro; Pedro Côrrea Damasceno Júnior; Alexandra Christine Helena Frankland Sawaya; Micheli da Silva Ferreira; Geni Rodrigues Sampaio; Elizabeth Aparecida Ferraz da Silva Torres; Tatiana Saldanha (Food Chemistry, 2023)

Integrative toolbox to assess the quality of freshwater sediments contaminated with potentially toxic metals - Patrícia Palma; Alexandra Marchã Penha; Maria Helena Novais; Sofia Fialho; Ana Lima; Adriana Catarino; Clarisse Mourinha; Paula Alvarenga; Maksim Iakunin; Gonçalo Rodrigues; Miguel Potes; Manuela Morais; et al. (Environmental Research, 2023)

Ambient vibration testing and seismic fragility analysis of masonry building aggregates - Vasco Miguel Serrano Bernardo; Alfredo Peres de Noronha Campos Costa; Paulo José de Oliveira Xavier Candeias; Aníbal Guimarães da Costa; Ana Isabel Mera Marques; Alexandra Rodrigues Carvalho (Bulletin of Earthquake Engineering, 2022)

Manganese(I) tricarbonyl complexes as potential anticancer agents - Oscar A. Lenis-Rojas; Beatriz Carvalho; Rui Cabral; Margarida Silva; Sofia Friães; Catarina Roma-Rodrigues; Marta S. H. Meireles; Clara S. B. Gomes; Jhonathan A. A. Fernández; Sabela F. Vila; Juan A. Rubiolo; Laura Sanchez; et al. (JBIC Journal of Biological Inorganic Chemistry, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

Emission inventory for harbour-related activities: comparison of two distinct bottom-up methodologies - Sandra Sorte; Vera Rodrigues; Rúben Lourenço; Carlos Borrego; Alexandra Monteiro (Air Quality, Atmosphere & Health, 2021)

A mixture of trehalose derivatives stimulates the antioxidant system and improves photosynthetic efficiency in maize under water deficit - Joice Aparecida de Novais Portugal; Alexandra dos Santos Ambrósio; Kamila Rezende Dázio de Souza; Danielle Ferreira Dias; Plínio Rodrigues dos Santos Filho; Thiago Belarmino de Souza; Marcelo Henrique dos Santos; Antonio Carlos Doriguetto; Paulo César Magalhães; Thiago Corrêa de Souza (Acta Physiologiae Plantarum, 2021)

Association between exposure to air pollution during intrauterine life and cephalic circumference of the newborn - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R. D. M. Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Environmental Science and Pollution Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Association between maternal exposure to air pollution before conception and sex determination in the city of São Paulo - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R D M Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Air Quality, Atmosphere & Health, 2020)

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Changes in salivary protein composition of lambs supplemented with aerial parts and condensed tannins: extract from Cistus ladanifer L.—a preliminary study - Elsa Lamy; Lénia Rodrigues; Olinda Guerreiro; David Soldado; Alexandra Francisco; Monica Lima; Fernando Capela e Silva; Orlando Lopes; José Santos-Silva; Eliana Jerónimo (Agroforestry Systems, 2020)

Correction to: In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

In vitro mechanistic studies on α-amanitin and its putative antidotes - Daniela Ferreira Rodrigues; Ricardo Pires das Neves; Alexandra T. P. Carvalho; Maria Lourdes Bastos; Vera M. Costa; Félix Carvalho (Archives of Toxicology, 2020)

Application of Systems Thinking to the assessment of an institutional development project of river restoration at a campus university in Southern Brazil - Fabiane Andressa Tasca; Roberto Fabris Goerl; Gean Paulo Michel; Nei Kavaguichi Leite; Djesser Zechner Sérgio; Saman Belizário; Jakcemara Caprario; Alexandra Rodrigues Finotti (Environmental Science and Pollution Research, 2020)

Detection of Zika virus in paired urine and amniotic fluid samples from symptomatic and asymptomatic women and their babies during a disease outbreak: association with neurological symptoms in newborns - Danila Vedovello; Steven S. Witkin; Andrea Cristina Botelho Silva; Thamirys Cosmo Gillo Fajardo; Alexandra Siqueira Mello; Ana Paula Antunes Pascalicchio Bertozzi; Alify Bertoldo da Silva; Nemésio Florence Vieira Filho; Maria Manoela Duarte Rodrigues; Rosa Estela Gazeta; Antônio Fernandes Moron; Stéphanno Gomes Pereira Sarmento; et al. (Journal of NeuroVirology, 2020)
Paired maternal and newborn urine and amniotic fluid from 138 subjects collected during a Zika virus (ZIKV) outbreak was analyzed for ZIKV by gene amplification (RT-qPCR), and the findings were correlated with clinical symptoms and neurological anomalies in the babies. ZIKV was detected in 1 of 9 symptomatic women (11.1%) and in 19 of 129 asymptomatic women (14.7%). Neurological manifestations were present in 19 babies (13.7%), 10 of 20 (50%) positive and 9 of 119 (7.6%) negative ( p < 0.001) for ZIKV. Twelve (8.6%) urines collected during gestation were ZIKV-positive; only 2 remained positive for ZIKV postpartum. Six (4.1%) newborn urines collected within 1 day of delivery were ZIKV-positive cases. In 3 of these cases, ZIKV was detected in mother’s urine pre- and postpartum and in both mother’s urine and babies’ urine. Four of the amniotic fluid samples (2.9%) were ZIKV-positive. Among ZIKV-negative babies with neurological sequel, 87.5% were female; in contrast, 72.7% ZIKV-positive babies with neurological abnormalities were male ( p = 0.019). We conclude that during a ZIKV outbreak, clinical symptoms and ZIKV detection in biological fluids are poor predictors of infection and adverse neurologic sequel in newborns.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Environmental impact of the on-road transportation distance and product volume from farm to a fresh food distribution center: a case study in Brazil - Gilson Tristão Duarte; Irenilza de Alencar Nääs; Cláudio Monico Innocencio; Alexandra Ferreira da Silva Cordeiro; Raquel Baracat Tosi Rodrigues da Silva (Environmental Science and Pollution Research, 2019)

(Cyto)genomic and epigenetic characterization of BICR 10 cell line and three new established primary human head and neck squamous cell carcinoma cultures - Ilda P. Ribeiro; Joana M. Rodrigues; Alexandra Mascarenhas; Vanessa Marques; Francisco Caramelo; Maria J. Julião; Thomas Liehr; Joana B. Melo; Isabel M. Carreira (Genes & Genomics, 2019)

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Cytological differentiation and cell wall involvement in the growth mechanisms of articulated laticifers in Tabernaemontana catharinensis A.DC. (Apocynaceae) - Yve Canaveze; Alexandra Antunes Mastroberti; Jorge Ernesto de Araujo Mariath; Silvia Rodrigues Machado (Protoplasma, 2019)

Tauroursodeoxycholic Acid Improves Motor Symptoms in a Mouse Model of Parkinson’s Disease - Alexandra Isabel Rosa; Sara Duarte-Silva; Anabela Silva-Fernandes; Maria João Nunes; Andreia Neves Carvalho; Elsa Rodrigues; Maria João Gama; Cecília Maria Pereira Rodrigues; Patrícia Maciel; Margarida Castro-Caldas (Molecular Neurobiology, 2018)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Numerical and physical assessment of control measures to mitigate fugitive dust emissions from harbor activities - Sandra Sorte; Vera Rodrigues; Ana Ascenso; Sylvio Freitas; Joana Valente; Alexandra Monteiro; Carlos Borrego (Air Quality, Atmosphere & Health, 2018)

Electrodialytic treatment of sewage sludge: influence on microbiological community - Paula Guedes; Nazaré Couto; Joana Almeida; António M. Rodrigues; Eduardo P. Mateus; Alexandra B. Ribeiro (International Journal of Environmental Science and Technology, 2018)

First Report on vanA-Enterococcus faecalis Recovered from Soils Subjected to Long-Term Livestock Agricultural Practices in Azores Archipelago - Vanessa Silva; Fernando Peixoto; Gilberto Igrejas; Carolina Parelho; Patrícia Garcia; Isabel Carvalho; Margarida Sousa; José Eduardo Pereira; Armindo Rodrigues; Patrícia Alexandra Curado Quintas D Poeta (International Journal of Environmental Research, 2018)

Life paths of patients with transthyretin-related familial amyloid polyneuropathy Val30Met: a descriptive study - Alice Lopes; Alexandra Sousa; Isabel Fonseca; Margarida Branco; Carla Rodrigues; Teresa Coelho; Jorge Sequeiros; Paula Freitas (Journal of Community Genetics, 2018)

Assessing in vivo digestibility and effects on immune system of sheep fed alfalfa hay supplemented with a fixed amount of Ulva rigida and Gracilaria vermiculophylla - Ana R. J. Cabrita; Alexandra Correia; Ana R. Rodrigues; Paulo P. Cortez; Manuel Vilanova; António J.M. Fonseca (Journal of Applied Phycology, 2017)

Water exchanges between a multi-inlet lagoon and the ocean: the role of forcing mechanisms - João Pedro Farinha Fabião; Marta Filipa Gomes Rodrigues; André Bustorff Fortunato; José Manuel Quintela de Brito Jacob; Alexandra Maria Francisco Cravo (Ocean Dynamics, 2016)

Fungi associated with rocks of the A tacama D esert: taxonomy, distribution, diversity, ecology and bioprospection for bioactive compounds - Vívian N. Gonçalves; Charles L. Cantrell; David E. Wedge; Mariana C. Ferreira; Marco Aurélio Soares; Melissa R. Jacob; Fabio S. Oliveira; Douglas Galante; Fabio Rodrigues; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; et al. (Environmental Microbiology, 2016)
Summary This study assessed the diversity of cultivable rock‐associated fungi from A tacama D esert. A total of 81 fungal isolates obtained were identified as 29 Ascomycota taxa by sequencing different regions of DNA. C ladosporium halotolerans , P enicillium chrysogenum and P enicillium cf. citrinum were the most frequent species, which occur at least in four different altitudes. The diversity and similarity indices ranged in the fungal communities across the latitudinal gradient. The F isher‐α index displayed the higher values for the fungal communities obtained from the siltstone and fine matrix of pyroclastic rocks with finer grain size, which are more degraded. A total of 23 fungal extracts displayed activity against the different targets screened. The extract of P . chrysogenum afforded the compounds α‐linolenic acid and ergosterol endoperoxide, which were active against C ryptococcus neoformans and methicillin‐resistance S taphylococcus aureus respectively. Our study represents the first report of a new habitat of fungi associated with rocks of the A tacama D esert and indicated the presence of interesting fungal community, including species related with saprobes, parasite/pathogen and mycotoxigenic taxa. The geological characteristics of the rocks, associated with the presence of rich resident/resilient fungal communities suggests that the rocks may provide a favourable microenvironment fungal colonization, survival and dispersal in extreme conditions.

Characterization of antiproliferative potential and biological targets of a copper compound containing 4′-phenyl terpyridine - Ana Soraia Mendo; Sara Figueiredo; Catarina Roma-Rodrigues; Paula A. Videira; Zhen Ma; Mário Diniz; Miguel Larguinho; Pedro M. Costa; João C. Lima; Armando J. L. Pombeiro; Pedro V. Baptista; Alexandra R. Fernandes (JBIC Journal of Biological Inorganic Chemistry, 2015)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Effect of ultraviolet-B radiation in laboratory on morphological and ultrastructural characteristics and physiological parameters of selected cultivar of Oryza sativa L. - Sérgio L. de Almeida; Éder C. Schmidt; Debora Tomazi Pereira; Marianne Kreusch; Marthiellen R. de L. Felix; Luz K. P. Osorio; Roberta de Paula Martins; Alexandra Latini; Fernanda Ramlov; Fungyi Chow; Marcelo Maraschin; Ana C. Rodrigues; et al. (Protoplasma, 2013)

Modeling fecal contamination in the Aljezur coastal stream (Portugal) - Marta Rodrigues; Anabela Oliveira; Martha Guerreiro; André Bustorff Fortunato; José Menaia; Luís Mesquita David; Alexandra Cravo (Ocean Dynamics, 2011)

Comparative environmental performance of semi-trailer load boxes for grain transport made of different materials - Cláudia Echevenguá Teixeira; Luciane Sartori; Alexandra Rodrigues Finotti (The International Journal of Life Cycle Assessment, 2010)